Improving the quality of silica sand as a proppant for hydraulic fracking industry purposes (Rudarsko-geološko-naftni zbornik, 2025)
A technological silica sand sample that belongs to "Egypt's Future Quarries", south west Cairo, was investigated as a proppant for the hydraulic fracking industry. The sample showed encouraging physical and mechanical characteristics, yet it was still in need of improving its grade to match the International Organization for Standardization specifications. After careful reading of the microscopy and mineralogy investigation of the head sample, a simple and cheap beneficiation flowsheet was suggested including sieve classification and an attrition scrubbing technique using a 50-liter capacity “Denver” machine. The results showed appreciable grade improvement in the attrition sand. An increase in silica content from 90.10% to 98.15% SiO2 at the expense of alumina and iron oxides %’s by 79% and 63%, respectively. This grade improvement subsequently led to notable improvement in turbidity and acid solubility measures and hence, transformed the sand sample from being unacceptable for the oil and gas industry to a sand product with acceptable specifications for this industry. The results also showed improvement in the crushability resistance and grain sphericity and roundness measures with ratios reaching 24.06%, 19.11% and 16.72%, respectively. In addition, particle size distribution of the attrition sand showed more consistency, which is desirable for the fracking industry.